Prevalence of mandibular third molar impaction and agenesis: A radiographic South Indian study - Ananthalakshmi Ramamurthy; Jeya Pradha; Sathiya Jeeva; Nadeem Jeddy; J Sunitha; Selva Kumar (Wolters Kluwer Medknow Publications, 2012)
Aims and objective: To evaluate the prevalence of (i) impaction of mandibular third molar, (ii) agenesis of mandibular third molar and (iii) angulation of impaction radiographically. Materials and methods: The sample size consists of 1,005 patients above 18 years. The orthopantomograph of the patients are interpreted for eruption/pattern of impaction/agenesis of mandibular third molar. Conclusion: Bilateral impaction of mandibular third molar is common than unilateral impaction. Agenesis of mandibular third molar is seen in 122 to 12.5% of patients. Mesioangular is the commonest pattern of impaction No sex predisposition is in prevalence of impaction. Agenesis is seen more commonly in females than males.